1989
DOI: 10.1111/j.1752-0606.1989.tb00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Patterns Associated With Anorexia Nervosa*

Abstract: A family systems perspective was used to explore familial transactional patterns related to anorexia nervosa. Father, mother and daughter, interpersonal assessments of parental initiative and daughter responsive behaviors as reported on Benjamin's (1974) Structural Analysis of Social Behavior (SASB), were combined to serve as data for a hierarchical cluster analysis. Out of the 22 families with an anorexic child and the 22 matched control families, 7 family groups with unique family dynamics differentiating on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The survey of the ways the patients and mothers rated their families by type supports the notion of possible different family patterns in families with anorectic young girls. It has already been suggested that families of anorectic patients are a heterogeneous group (Garfinkel et al, 1983;Grigg & Friesen, 1989;Dare et al, 1995). Our study supports this idea, as well as the distinction between the restrictive and bulimic type of anorexia nervosa.…”
supporting
confidence: 91%
“…The survey of the ways the patients and mothers rated their families by type supports the notion of possible different family patterns in families with anorectic young girls. It has already been suggested that families of anorectic patients are a heterogeneous group (Garfinkel et al, 1983;Grigg & Friesen, 1989;Dare et al, 1995). Our study supports this idea, as well as the distinction between the restrictive and bulimic type of anorexia nervosa.…”
supporting
confidence: 91%
“…Another more compelling possibility is that the range of family dysfunction present in such families may be quite wide, with some families functioning at very high and a much smaller group at very low levels. This would be supported by some empirical work (Kog & Vandereycken, 1989;Humphrey, 1989;Grigg et al, 1989). It may also be that some theoretical models may have been based on observations of biased samples, biased perhaps by the well-known expertise of the theorists in dysfunctional families.…”
Section: Scu Sslonmentioning
confidence: 91%
“…The most methodologically sophisticated studies (Humphrey, 1989;Grigg et al, 1989;Kog & Vandereycken, 1989) have supported a finding of considerable variation in reported family functioning, with some families functioning at very high levels. Most studies have reported that patients rate their own families as very disturbed.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Grigg and Friesen (1989) and by Marcus and Wiener (1989), which focused entirely on eating disorders, offer additional support to the contentions by Anderson (1988, 1989). Although they found that families with an anorexic child did differ from control families on a number of dimensions, this could by no means be interpreted as evidence for the existence of an anorexogenic family structure.…”
Section: Eating Disorders and Psychosomaticsmentioning
confidence: 64%